2016
DOI: 10.4103/2045-9912.179342
|View full text |Cite
|
Sign up to set email alerts
|

Gas transport during in vitro and in vivo preclinical testing of inert gas therapies

Abstract: New gas therapies using inert gases such as xenon and argon are being studied, which require in vitro and in vivo preclinical experiments. Examples of the kinetics of gas transport during such experiments are analyzed in this paper. Using analytical and numerical models, we analyze an in vitro experiment for gas transport to a 96 cell well plate and an in vivo delivery to a small animal chamber, where the key processes considered are the wash-in of test gas into an apparatus dead volume, the diffusion of test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Note that we cannot exclude, however, that favorable PK properties also contributed to the efficacy of xenon. In particular, in this in vitro experimental set-up, the concentrations of xenon at the level of the cell layer and the time necessary to reach these concentrations may be important factors for neuroprotection (Katz et al 2016). Theoretical calculations made with gaseous atmospheres containing noble gases at a concentration of 50%, revealed that xenon was the slowest of all these gases to saturate the culture medium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that we cannot exclude, however, that favorable PK properties also contributed to the efficacy of xenon. In particular, in this in vitro experimental set-up, the concentrations of xenon at the level of the cell layer and the time necessary to reach these concentrations may be important factors for neuroprotection (Katz et al 2016). Theoretical calculations made with gaseous atmospheres containing noble gases at a concentration of 50%, revealed that xenon was the slowest of all these gases to saturate the culture medium.…”
Section: Discussionmentioning
confidence: 97%
“…The mathematical model and experimental parameters used to perform calculations have been described in detail in one of our previous papers (Katz et al 2016). In brief, the transport of the Noble gas through the liquid medium to the cells is modeled as a one-dimensional diffusion problem:…”
Section: Mathematical Modeling Of Gas Diffusion In Culture Wellsmentioning
confidence: 99%
“…Exposure of cell to gasses has been designed inspired from previously described methods of NO administration (Miller et al, 2009b) integrating lessons learnt from our models of in vitro gas exposure [ 26 ]. Infected cells were placed within hermetically sealed Plexiglas incubation chambers (220 × 220 × 194mm) with separate gas entry and exit ports allowing a continuous flow of gaseous NO through the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, only a small percentage of this NO will be available to cells. In particular, the solubility of NO in the cell medium (the Ostwald solubility coefficient in water for NO is 0.04128 [ 28 ] ( Table 1 , pg 229) is a ceiling on the potential exposed concentration [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study employs a physiologically based pharmacokinetic model developed by Lockwood 7 for anesthetic gases that has been employed within the Simbiology Toolbox of MATLAB (Mathworks, Natick, MA, USA). 8 The model considers all transport to be perfusion limited, that there is no metabolism, and all excretion is through expiration via the lung. Here we present the partition coefficients for N 2 ( Table 1 ) and a detailed explanation of the compartment consisting of the alveolar gas exchange region of the lung ( Figure 1 ) as these are the results comparable to the published experimental data by Lundin.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%